Possibilities and benefits of an extension of the border integration area with Chile beyond Tacna and Arica - Quispe Sandoval, Mijail (2020)
The Binational Peru-Chile Cabinet held in July 2019 laid the possibility of broadening the border space between the two countries, beyond the consolidated area shaped by Tacna and Arica. The hypothesis to be tested is that a greater involvement of the contiguous regions of Moquegua and Tarapaca in bilateral forums and an "expanded vision of the binational border region" –southern Peru-northern Chile, will promote mutual benefits for both countries, in specific areas like tourism, prevention of transnational crimes, cultural, academic, and economic relations, among others.